Variations in leukocyte Acute Exposure to High Altitude - Anduaga Merino, Germán (1968)
This study was conducted in native subject of sea level, healthy, between 20 and 30 years old, in which basal blood samples were taken at sea level and then were taken to Morococha (4,500 meters above at sea level)  where serial blood samples were taken at 6 - 8 -18 - 24 - 48 -72 - 96 - 120 - 144 -168 hours after ascent. Leukocyte count and differential are performed Schilling formula, calculating the absolute values ​​of leukocytes per mm2 in all subjects. We found that all series of cells had an increase in the first 6 hours in the small lymphocyte s ascent continued until 18 hours before dropping sharply. The values ​​of all elements were descending to 8 days were made similar to those who had at sea level.